“KATAMIAˮ (Kader Tangani Anemia) dalam Upaya Penanganan Anemia pada Ibu Hamil di Wilayah Kerja Puskesmas Dirgahayu - Satsiwi Wahyu Widi Handayani; Rena Herlena; Fadhiyah Noor Anisa; Istiqamah Istiqamah (PPNI UNIMMAN, 2024)
Prevention of anemia in pregnant women can be done with appropriate health behavior. Health behaviors such as maintaining a diet high in iron, regularly consuming iron tablets, and carrying out ANC during early pregnancy can reduce the prevalence of anemia in pregnant women. Diet is an important factor that pregnant women must pay attention to. Poster media is one media that has a lot of information about the diversity of foods that are useful for preventing anemia and can be used to help carry out health education. Create